The Occupational Safety and Health Protection for Health Workers during the Covid-19 Pandemic at AMC Hospital Yogyakarta - Nazzela Jeanny Andrian; Endriyo Susila (Unnes Law Journal, 2023)
The Corona Virus Disease 2019 (Covid-19) pandemic has affected almost all sectors, especially health sector. Standing in the forefront in handling the Covid-19 patients, healthcare workers are exposed to the high risk of virus transmission. Therefore, Occupational Safety and Health (OSH) protection of healthcare workers should also get serious attention from various parties, especially employers. AMC hospital is one of the healthcare facilities in Yogyakarta that is engaged in the fight against the Covid-19 outbreak. The aim of this research is to explore the way AMC Hospital implement the occupational safety and health protection for its healthcare workers during the Covid-19 Pandemic. The type of this research is empirical legal research which examines the application of relevant legal provisions in regard to the issue of occupational safety and healthcare protection for healthcare workers in AMC Hospital Yogyakarta. The results of the study show that AMC hospital successfully implemented OSH during the pandemic in an effort to protect healthcare workers. Further, Occupational Diseases (PAK) caused by Covid-19 are covered by the Work Accident Insurance (JKK) program and the Social Health Insurance Administration Body (BPJS) in compliance with legal requirements.